Online news consumption in Kenya: emerging and receding patterns among young people - Tallam, Edwin (My University, 2020)
This thesis explores news consumption patterns and habits among young people in Kenya. While there is a widespread agreement that the internet and mobile devices have reconfigured the mediascape in the Global South, it is not yet clear how the adoption and adaptation of both have shaped content (including news). Instead, much effort has been expended on how the relatively high internet and mobile penetration rates could ‘transform’ and possibly help states in the Global South, achieve their development goals. In addition, existing literature has devoted attention to how traditional news organisations have embraced social media and messaging applications in their routine news gathering, processing and dissemination practices. This approach has obscured rather than reveal the news users’ experiences, particularly the kind of news genres accessed and consumed. It also underplays the motives behind such choices, against the proliferation of 'fake' news. In this regard, I combined the rooted Uses and Gratifications theory (U and G) and the relatively new concept of “scalable sociality” as the two main pillars of an original framework aimed at analysing and explaining young people’s agency in news consumption. Uses and gratifications was particularly useful in framing research questions on news access and the enablers of the high mobile and internet penetration rates in Kenya. On the other hand, Scalable sociality was valuable in illuminating online news consumption processes––including how news mutates across public and private spaces of socialities. The non-normative third wave African scholarship was embraced to explain unfamiliar news use and Sponsors: Enter the names of any sponsors and/or funding codes in the box. consumption patterns among young people. This study embraced a mixed-methods approach. The first phase was a survey involving 800 respondents in two academic institutions. The objective of the survey was to map the emerging and receding patterns of news consumption. The second phase comprised of eight focus group discussions (FGDs) aimed at nuancing the emerging themes of news consumption revealed by the survey. Lastly, ethnographic methods (online and offline observations) were useful in providing a more holistic understanding of how internet-enabled mobile devices are interwoven in the daily lives and news consumption experiences of young people. Findings revealed how news consumption among young people in Kenya is a complex and multi-layered process, often defying pre-existing conceptions. While statistics on the internet and mobilepenetration rates tend to be used to frame Kenya as a leading country in the African digital space, these obscure the specific ways in which young people creatively navigate barriers to access, through hacking and developing parallel markets for cheap bundles. Regarding the content that is consumed on social media, the prevalent news sub-genre is political news. Paradoxically, young people consume political news not to become responsible civic agents, but rather for their entertainment value. They enjoy the ‘drama’ staged by political leaders as they transgress their private lives in public spaces. Therefore, while news exposure occurs across public and private platforms, news deliberations occur on ephemeral private platforms such as WhatsApp. Finally, the perceived prevalence of ‘fake news’ on social media has increased the stakes of traditional media (radio, newspapers and television) as the most trusted news sources online and offline
A PhD thesis submitted in (partial) fulfilment of the requirements for the award of a Doctor of Philosophy degree in Media Studies, at the University of the Witwatersrand, 2020